Admissibility of evidence before the Inter-American Court of Human Rights - Álvaro Paúl (Revista Direito GV)
Abstract The Inter-American Court of Human Rights performs a wide evidentiary analysis, which tends to be very flexible in its admission of evidence. This paper tries to decipher the extent, applicability, and content of the Court’s admissibility rules, both the norms established by the Court itself, and those that the Court is obliged to follow. In order to do so, this article will analyze the relevant case law of the Court and provide some examples. Within this analysis, this article refers in depth to some unclear rulings that the Court has made in relation to the exclusion of evidence obtained via coercion, some of which seem to clash with the central role of truth in the Inter-American system.